PEMBELAJARAN BERBASIS PROYEK (PROJECT-BASED LEARNING) UNTUK MENGEMBANGKAN KETERAMPILAN ABAD 21 - Taufiqurrahman, Taufiqurrahman; Junaidi, Junaidi (INCARE, International Journal of Educational Resources, 2021)
21st century skills, related to Education include communication, collaborative, critical thinking, problem solving, creative and innovative skills adapted in the competency curriculum. 21st century skills are seen as skills needed for success in life in the 21st century. The embodiment of this skill adaptation is in a learning approach that emphasizes inquiry, which aims to develop scientific abilities and attitudes. In the writing will examine project-based learning, as one of the inquiry-oriented learning approaches. The presence of PjBL as a method of learning that is student-centered and emphasizes inquiry (research), experiencing rejection and criticism from groups that emphasize the importance of students' mastery of certain materials in certain subjects. Even so, learning that emphasizes deeper learning and the development of skills needed for success in college, career and community life becomes popular. Many educational institutions adopt this method.